2014
DOI: 10.1016/j.tube.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide susceptibility testing of Mycobacterium tuberculosis by high resolution melt analysis

Abstract: Pyrazinamide (PZA) plays the important role in shortening the tuberculosis treatment period and in treating MDR-TB. Phenotypic PZA susceptibility methods are limited because they require specialized acidified media, which increases costs and complexity. In this study we developed a genotypic high resolution melt (HRM) analysis technique to detect pncA mutations associated with PZA resistant M. tuberculosis. Seven overlapping primer pairs were designed to cover the entire pncA gene and upstream regions. Each ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Interestingly, the HRM assay could delegate them only as mutants (single mutant curve), indicating that sequencing is a better tool for detecting the heteroresistant pattern if present. Similar findings have been reported previously in an HRM assay for pyrazinamide resistance detection (46). Heteroresistance has been identified previously in many studies using DNA sequencing (47,48).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the HRM assay could delegate them only as mutants (single mutant curve), indicating that sequencing is a better tool for detecting the heteroresistant pattern if present. Similar findings have been reported previously in an HRM assay for pyrazinamide resistance detection (46). Heteroresistance has been identified previously in many studies using DNA sequencing (47,48).…”
Section: Discussionsupporting
confidence: 89%
“…[1] that fast genotypic methods will play an increasingly prominent role in drug-susceptibility testing (DST) for the Mycobacterium tuberculosis complex (MTBC) [2]. They reported on the evaluation of a high-resolution melt assay (HMR) to detect pyrazinamide (PZA) resistance, which has the advantage of speed and simplicity.…”
mentioning
confidence: 99%
“…This observation has been proven elsewhere [25]. PZA phenotypic susceptibility testing by the Bactec MGIT 960 is normally carried out at pH of 5.9, resistance could be falsely reported as a result of the ammonia produced during mycobacterial growth; ammonia elevates the pH of the media thus inactivating the drug [26]. According to the Henderson-Hasselbalch equation, M. tuberculosis should be tested for PZA susceptibility at a concentration of at least 156 µg/ml [10], rather than the current cut-off used in the Bactec MGIT 960 method (100 µg/ml).…”
Section: Discussionmentioning
confidence: 78%
“…So far, only one study has utilized the Roche LightCycler 480 ® for PZA susceptibility testing and used the Bactec MGIT 960 as a reference method [42]. They have shown a sensitivity and specificity of 85.5% and 98.5%, respectively and concluded that HRM is a rapid and accurate test for the detection of PZA resistance and can be used as a screening method [26]. However, recently, HRM results generated from the Rotor-gene system for the detection of PZA resistance have been found to be easier to interpret than other platforms [25].…”
Section: Discussionmentioning
confidence: 99%